O025 Unopposed interleukin 18 signalling leads to severe toll like receptor 9-induced macrophage activation syndrome in mice. (21st February 2018) - Girard-Guyonvarc'h, C; Palomo, J; Martin, P; Rodriguez, E; Troccaz, S; Palmer, G; Gabay, C
Abstract : Introduction: Macrophage activation syndrome (MAS) is a severe condition, which can appear as a complication of inflammatory rheumatic diseases such as systemic juvenile idiopathic arthritis (sJIA) and adult onset Still's disease (AOSD), a viral infection, or a malignancy. Interleukin (IL)−18 is a pro-inflammatory cytokine of the IL-1 family, known as a strong interferon (IFN)-γ inducer, that is naturally inhibited by IL-18 binding protein (IL-18BP). High levels of unbound biologically active IL-18 have been described in patients with sJIA, AOSD, and MAS, suggesting that IL-18 is involved in the pathogenesis of these diseases. Objectives: To examine the effect of excessive IL-18 signalling in a mouse model of MAS induced by repetitive toll like receptor (TLR)9 stimulation, and explore the consequences of IL-18 or IFN-γ blockade on MAS manifestations. Methods: MAS was induced by repeated intraperitoneal CpG injections in IL-18BP deficient ( IL-18BP -/- ) mice and in wild type (WT) littermates. Anti-IL-18 receptor (IL-18R) or anti-IFN-γ monoclonal antibodies were administered prior to CpG injections. Clinical and biological manifestations of MAS were studied. Plasma levels of free IL-18 were measured by ELISA. Expression levels of IFN-γ and downstream IFN-γ-induced effectors (CXCL9, CIITA) were explored by ELISA or Luminex in plasma, and by RT-qPCR in spleen and liver. Results: Naïve IL-18BP -/- mice had no spontaneous phenotype. After repeated CpG injections, IL-18BP -/- mice displayed significantly more severe MAS phenotype than their WT littermates, including more pronounced weight loss, splenomegaly, anaemia, thrombocytopenia, hyperferritinemia and hepatitis. This phenotype was associated with elevated plasma levels of unbound IL-18 and the presence of bone marrow hemophagocytes in IL-18BP -/- mice only. In addition, IL-18BP -/- mice displayed higher plasma levels of IFN-γ and CXCL9, as well as increased Ifnγ, Cxcl9 and CIIta mRNA expression in the spleen and liver. IL-18 blockade using an anti-IL-18R antibody attenuated MAS manifestations in IL-18BP -/- mice and abrogated IFN-γ production and downstream signalling. IFN-γ blockade using an anti-IFN-γ antibody also attenuated the MAS phenotype. Conclusions: By using IL-18BP -/- mice, we showed that unopposed IL-18 signalling was detrimental in the TLR9-induced MAS model. Importantly, blocking IL-18, as well as IFN-γ, improved disease in IL-18BP -/- mice. Altogether, our results suggest that IL-18 exerts a pathogenic role in this model of MAS, acting upstream of IFN-γ. Disclosure of interest: None declared